Virtual reality in the classroom: a difficult but exciting adventure for teachers and students - Rodríguez, José L. (Frontiers in Education, 2024)
Virtual reality (VR) enables the creation of immersive and interactive learning environments for students and teachers. This article reports on an exploratory teaching practice conducted with pre-service secondary school teachers using Neotrie, a dynamic geometry software in virtual reality. In small groups, future teachers must learn how to use the software and design a didactic sequence to bring to the classroom. Following a research-action methodology, through this experience it is reported both the advantages and difficulties encountered when starting to use VR to design didactic sequences, as well as when learning a VR sandbox software with interactive tools, like Neotrie. A proposal for assessing the sequences under the premises of the TPaCK model is also included.